ImaSim, a software tool for basic education of medical x-ray imaging in radiotherapy and radiology - landry, guillaume; deblois, francois; Verhaegen, Frank (Frontiers in Physics, 2013)
Introduction: X-ray imaging is an important part of medicine and plays a crucial role in radiotherapy. Education in this field is mostly limited to textbook teaching due to equipment restrictions. A novel simulation tool, ImaSim, for teaching the fundamentals of the x-ray imaging process based on ray-tracing is presented in this work. ImaSim is used interactively via a graphical user interface (GUI). Materials and methods: The software package covers the main x-ray based medical modalities: planar kilovoltage (kV), planar (portal) megavoltage (MV), fan beam computed tomography (CT), and cone beam CT (CBCT) imaging. The user can modify the photon source, object to be imaged and imaging setup with three-dimensional editors. Objects are currently obtained by combining blocks with variable shapes. The imaging of three-dimensional voxelized geometries is currently not implemented, but can be added in a later release. The program follows a ray-tracing approach, ignoring photon scatter in its current implementation. Simulations of a phantom CT scan were generated in ImaSim and were compared to measured data in terms of CT number accuracy. Spatial variations in the photon fluence and mean energy from an x-ray tube caused by the heel effect were estimated from ImaSim and Monte Carlo simulations and compared. Results: In this paper we describe ImaSim and provide two examples of its capabilities. CT numbers were found to agree within 36 Hounsfield Units (HU) for bone, which corresponds to a 2% attenuation coefficient difference. ImaSim reproduced the heel effect reasonably well when compared to Monte Carlo simulations. Discussion: An x-ray imaging simulation tool is made available for teaching and research purposes. ImaSim provides a means to facilitate the teaching of medical x-ray imaging.